Optimalisasi Produksi Listrik PLTA Sutami Berdasarkan Ketersediaan Energi Primer - Hasyyati Zakirah Masturah; Subairi Subairi; Rahman Arifuddin (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
The Sutami Hydroelectric Power Plant managed by PLN Nusantara Power UP Brantas is one of the power plants that relies on air resources to generate electricity. However, the optimization of electricity production can still be improved by considering the availability of primary energy and the interests of related stakeholders. This study aims to create a simulation of operating patterns to optimize the daily electricity production of the Sutami Hydroelectric Power Plant using the MS Excel Solver program. The total electrical energy in March based on the results of the simulation calculation was 56,537,445.55 MWh, 3.09% greater than the actual data of 54,792,800 MWh. The results of the simulation calculation of electricity production in June 2024 were 27,564,315.75 MWh, 3.82% greater than the actual data of 26,511,800 MWh. In FDC 2014-2023, the average mainstay discharge is 32 m3/s available throughout the year to be utilized by water turbines to produce a minimum power of 20 MW. Meanwhile, from the estimated historical data obtained by FDC 2024-2033 with an average mainstay discharge of 40.68 m3/s to produce a minimum power of 30 MW.